RESEARCH INFRASTRUCTURE SPECIALIZED SCIENTIFIC ORGANIZATION - S. Ulanin (Вестник университета)
It classifies the infrastructure of the scientific organization. The basic components of the scientific organization of infrastructure and intellectual labor, cultural and spiritual, legal, logistical, organizational and managerial. Presented unconventional factors motivating knowledge workers specialized scientific organizations. Substantiated and shows the composition of the regional organization of specialized scientific research infrastructure.